Repellent Ability of Encapsulated Guava Leaves Extract and Horticultural Mineral Oil (HMO) on the Feeding Behaviour of Diaphorina citri - Poerwanto, Mofit Eko; Danar, Wicaksono; Ajri, Miftahul; Ulilalbab, Azizah Ridha (Bogor Agricultural University, Indonesia, 2026)
Repellency is one of strategies to reduce Diaphorina citri attack. Guava leaf extract (GLE) and horticultural mineral oil (HMO) are well-known as repellents against D. citri but have short persistence. This research was conducted to increase the persistence of GLE and HMO extracts by using simultaneous co-delivery as part of environmentally friendly control of D. citri. The treatments used were 5% GLE, 5% HMO, 5% GLE + 5% HMO, 5% encapsulated GLE, 5% encapsulated HMO, 5% encapsulated GLE + 5% encapsulated HMO, and aquadest as control. The result shows that 5% HMO, 5% GLE + 5% HMO, and 5% encapsulated GLE have a repellency effect on D. citri. In the non-encapsulated treatments, the percentage of D. citri stayed at treated citrus leaves increased significantly at 9 and 12 hours after application except 5% GLE + 5% HMO. Exposure to 5% GLE, 5% HMO, and 5% encapsulated GLE. The most dominant of GLE compounds was lactose and d-Glycero-l-gluco-heptose. The most dominant of HMO compounds were 17-Pentatriacontene, Tetrapentacontane 1,54-dibromo- and tert-Hexadecanethiol. Encapsulation of 5% GLE can increase the persistence of GLE as a repellent compound for D. citri, but this effect does not occur in HMOs.